TUGAS POKOK DAN FUNGSI (TUPOKSI) SATUAN POLISI PAMONG PRAJA (SATPOL PP) TENTANG PERATURAN DAERAH NO 15 TAHUN 2005 DI KOTA PONTIANAK - Doewiono Sasputro E.01106048 (FISIP Universitas Tanjungpura, 2013)
This article was triggered by desire to know the enforcement of regulations done by Satpol pp Pontianak City to regulation No. 15/2005 about gaming kite. Formulation problem of this research is